Competitiveness of city geo-brand assessment: selecting the research methodology - I. Yu. Aleksandrova (Вестник университета)
The article studies the problem of selecting the research methodology of a city geo-brand in order to identify the optimal methodological tools for assessing its competitiveness. The author’s interpretation of a city geo-brand concept has been offered, the features of a city geo-brand concept choice, algorithm of its assessment, and evaluation parameters diagnostics methods analyzed. The comparative analysis of the current geo-brand competitiveness estimation models has been made. The study concludes the main reasons for the variety of a city geo-brand estimation models and optimal type of competitiveness assessment ones along with approach to the choice of parameter estimation diagnostics methods and universal system of evaluation parameters development.